Aquatic exercise training and stable heart failure: A systematic review and meta-analysis. (1st May 2015) - Adsett, Julie A.; Mudge, Alison M.; Morris, Norman; Kuys, Suzanne; Paratz, Jennifer D.
Abstract: Aim: A meta-analysis and review of the evidence was conducted to determine the efficacy of aquatic exercise training for individuals with heart failure compared to traditional land-based programmes. Methods: A systematic search was conducted for studies published prior to March 2014, using MEDLINE, PUBMED, Cochrane Library, CINAHL and PEDro databases. Key words and synonyms relating to aquatic exercise and heart failure comprised the search strategy. Interventions included aquatic exercise or a combination of aquatic plus land-based training, whilst comparator protocols included usual care, no exercise or land-based training alone. The primary outcome of interest was exercise performance. Studies reporting on muscle strength, quality of life and a range of haemodynamic and physiological parameters were also reviewed. Results: Eight studies met criteria, accounting for 156 participants. Meta-analysis identified studies including aquatic exercise to be superior to comparator protocols for 6 minute walk test (p < 0.004) and peak power (p < 0.044). Compared to land-based training programmes, aquatic exercise training provided similar benefits for VO2peak, muscle strength and quality of life, though was not superior. Cardiac dimensions, left ventricular ejection fraction, cardiac output and BNP were not influenced by aquatic exercise training. Conclusions: For those with stable heart failure, aquatic exercise training can improve exercise capacity, muscle strength and quality of life similar to land-based training programmes. This form of exercise may provide a safe and effective alternative for those unable to participate in traditional exercise programmes. Highlights: Aquatic exercise improves exercise capacity and QoL for those with HF. Improvements in exercise capacity are similar to those from land based training. Aquatic exercise is safe for people with stable HF. Aquatic exercise is an effective alternative to land based exercise training. Further research is warranted.